STRATEGI KEPEMIMPINAN KEPALA KEMENTERIAN AGAMA DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH ALIYAH DI KOTA BIMA - MAR’IN, MUHAMMAD; HASAN, MARDIAH; MARDYAWATI, MARDYAWATI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
This research is an explanatory research with a qualitative method, an Islamic education management approach. The data collection method is carried out by interviewing the head and section of the madrasah education of the Ministry of Religion of Bima City and the head of MAN 1 and MAN 2 of Bima City, in addition to observation and documentation. The data sources used are primary and secondary data. Data management and data analysis techniques are carried out through three stages, namely data reduction, data presentation and drawing conclusions. Data validity testing through extension of research time, observation fear, triangulation, and reference adequacy. The results of this study indicate that the implementation of madrasah aliyah in Bima City is committed to continuous professional development for teachers. This includes regular training, workshops, and seminars that focus on the latest teaching techniques and development of pedagogical competence. We also encourage teachers to take additional courses and certification programs that are relevant to their fields. Through this professional development, we hope that teachers can continue to improve their skills and provide high-quality education. Evaluation of the leadership strategy of the head of the Ministry of Religion in improving the quality of education in Islamic high schools in Bima City, namely the problem of human resources and also the problem of facilities and infrastructure, which then this core problem will affect the four standards. ABSTRAKPenelitian ini merupakan jenis penelitian eksplanatori dengan metode kualitatif, pendekatan management of Islamic education. Adapun metode pengumpulan data dilakukan dengan cara wawancara terhadap kepala dan seksi pendidikan madrasah kementerian agama kota bima dan kepala MAN 1 dan MAN 2 kota Bima, selain itu observasi dan dokumentasi. Sumber data yang digunakan adalah data primer dan sekunder. Tekhnik pengelolaan data dan analisis data dilakukan melalui tiga tahapan yaitu reduksi data, penyajian data dan penarikan kesimpulan. Uji keabsahan data melalui perpanjangan waktui penelitian, ketekutan pengamatan, triangulasi, dan kecukupan referensi. Hasil penelitian ini menunjukan pelaksanaan madrasah aliyah di Kota Bima berkomitmen untuk pengembangan profesional berkelanjutan bagi para guru. Ini mencakup pelatihan rutin, workshop, dan seminar yang berfokus pada teknik pengajaran terbaru dan pengembangan kompetensi pedagogik. Kami juga mendorong guru untuk mengikuti kursus tambahan dan program sertifikasi yang relevan dengan bidang mereka. Melalui pengembangan profesional ini, kami berharap guru dapat terus meningkatkan keterampilan mereka dan memberikan pendidikan berkualitas tinggi. Evaluasi strategi kepemimpinan kepala kementerian agama dalam meningkatkan mutu pendidikan madrasah aliyah di Kota Bima yaitu masalah sumber daya manusia dan juga masalah sarana dan prasarana yang kemudian masalah inti ini akan mempengaruhi dari empat standar.